Intraspecies cell–cell communication in yeast. Issue 7 (5th November 2019) - Yashiroda, Yoko; Yoshida, Minoru
ABSTRACT: Although yeasts are unicellular microorganisms that can live independently, they can also communicate with other cells, in order to adapt to the environment. Two yeast species, the budding yeast Saccharomyces cerevisiae and the fission yeast Schizosaccharomyces pombe, engage in various kinds of intraspecies cell–cell communication using peptides and chemical molecules that they produce, constituting a sort of 'language'. Cell–cell communication is a fundamental biological process, and its ultimate purpose is to promote survival by sexual reproduction and acquisition of nutrients from the environment. This review summarizes what is known about intraspecies cell–cell communication mediated by molecules including mating pheromones, volatile gases, aromatic alcohols and oxylipins in laboratory strains of S. cerevisiae and S. pombe . Abstract : This review gives an overview of intraspecies cell–cell communication in Saccharomyces cerevisiae and Schizosaccharomyces pombe .